2023
DOI: 10.1002/ptr.7723
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin, a dietary flavonoid, increases the sensitivity of chemoresistant head and neck carcinoma cells to cisplatin possibly through HSP90AA1/IL‐17 pathway

Abstract: Cisplatin (DDP) resistance is a bottleneck in the treatment of head and neck cancer (HNC), leading to poor prognosis. Fisetin, a dietary flavonoid, has low toxicity and high antitumor activity with unclear mechanisms. We intended to predict the targets of fisetin for reversing DDP‐resistance and further verify their expressions and roles. A network pharmacology approach was applied to explore the target genes. The hub genes were screened out and subjected to molecular docking and experimental verification (in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…HSP90AA1 was highly expressed in various tumors and significantly correlated with poor prognosis [ 45 ]. HSP90AA1/IL-17 signaling pathway was associated with cisplatin resistance in head and neck squamous carcinoma [ 46 ]. MAP2K1 activation is implicated in several malignancies and is a therapeutic target in HNSCC [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…HSP90AA1 was highly expressed in various tumors and significantly correlated with poor prognosis [ 45 ]. HSP90AA1/IL-17 signaling pathway was associated with cisplatin resistance in head and neck squamous carcinoma [ 46 ]. MAP2K1 activation is implicated in several malignancies and is a therapeutic target in HNSCC [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The low-dose irradiation induces expression of IL-17 in tumor beds and enhances the growth of subsequently implanted tumor cells, while treatment with anti-IL-17 antibody abolished the acceleration of tumor growth, confirming the key role of IL-17 in enhancing tumor growth in pre-irradiated tumor beds [ 170 ]. Interleukin-17 plays a role in restoration of the damaged epithelia in radiation induced oral mucositis and attenuates epithelial damage [ 171 ], which imply that a similar IL-17 mediated process could contribute to better recovery of OSCC cells after radiotherapy and eventually chemotherapy and subsequently contribute to resistance of oral squamous cancer to therapy. Flavonoid induced better sensitivity of chemo-resistant OSCC cells to cisplatin is accompanied by the downregulation of IL-17 [ 171 ].…”
Section: Il-17 and Cancer Therapymentioning
confidence: 99%
“…Interleukin-17 plays a role in restoration of the damaged epithelia in radiation induced oral mucositis and attenuates epithelial damage [ 171 ], which imply that a similar IL-17 mediated process could contribute to better recovery of OSCC cells after radiotherapy and eventually chemotherapy and subsequently contribute to resistance of oral squamous cancer to therapy. Flavonoid induced better sensitivity of chemo-resistant OSCC cells to cisplatin is accompanied by the downregulation of IL-17 [ 171 ]. Moreover, in the mouse model of OSCC, it has been shown that inhibition of IL-17A combined with the PD-1 blockade delayed the development of precancerous and cancerous lesions and prolonged the survival of 4NQO-treated mice, suggesting the IL-17A blockade as a potential approach to augment the tumor eliminating effects of anti-PD-1 therapy [ 92 ].…”
Section: Il-17 and Cancer Therapymentioning
confidence: 99%
“…These compounds are frequently found in combination with sugars, forming glycosides. Over the years, avonoids have been extensively investigated for potential applications in medicines (Zhang and Yan 2023) and pharmaceuticals (Johan et al 2023), as well as natural health foods and beverages (Oei et al 2023), because they have demonstrated anti-in ammatory, antiviral, antioxidant, and anticancer properties and are nontoxic (Ling et al 2023;Peng et al 2023). They are also utilized in agricultural production and animal husbandry (Schnarr et al 2022;Lin et al 2022).…”
Section: Introductionmentioning
confidence: 99%